2013
DOI: 10.1128/aem.01761-13
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Biosynthesis of Unsaturated Fatty Acids in Bacillus cereus ATCC 14579 and Functional Characterization of Novel Acyl-Lipid Desaturases

Abstract: At low temperatures, Bacillus cereus synthesizes large amounts of unsaturated fatty acids (UFAs) with double bonds in positions ⌬5 and ⌬10, as well as ⌬5,10 diunsaturated fatty acids. Through sequence homology searches, we identified two open reading frames (ORFs) encoding a putative ⌬5 desaturase and a fatty acid acyl-lipid desaturase in the B. cereus ATCC 14579 genome, and these were named BC2983 and BC0400, respectively. Functional characterization of ORFs BC2983 and BC0400 by means of heterologous expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 28 publications
1
28
1
Order By: Relevance
“…The genes encoding the two desaturases DesA and DesB were also downregulated in the ΔcasK/R strain compared to the WT strain. These B. cereus desaturases are responsible for UFA biosynthesis (Chazarreta Cifre et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genes encoding the two desaturases DesA and DesB were also downregulated in the ΔcasK/R strain compared to the WT strain. These B. cereus desaturases are responsible for UFA biosynthesis (Chazarreta Cifre et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Basically, the proportion of Δ5-UFAs, which are specifically unsaturated by DesA, was higher in the WT strain than in the ΔcasK/R strain. B. cereus DesA is a Δ5 desaturase homologous to B. subtilis Des protein (Chazarreta Cifre et al, 2013) that catalyzes the fixation of double bonds in the Δ5 position on FA. An extensive investigation of the biosynthesis of UFAs in Bacilli (Fulco, 1969) showed that for some Bacillus species that synthesize Δ5 UFAs, such as B. megaterium and B. subtilis, proportion of Δ5-UFAs increases when the bacteria are grown at low temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of desaturases varies depending on species, e.g. two desaturases have been identified in Bacillus cereus stricto or ss [ 10 ] whereas B. subtilis counts only one known desaturase [ 11 ]. The FA composition of bacterial cells is also known to vary according to species, especially in Bacillus and related genera [ 12 , 13 ], and has been included among important features for describing new taxa of the aerobic endospore-forming bacteria [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using similar pathways1212, many Gram-positive organisms, such as the bacillus, staphylococci, and streptomycetes, are able to produce BCFAs with odd- and even-numbered carbon chains13141516. However, the substrate specificity of 3-ketoacyl-acyl carrier protein (ACP) synthase III (FabH) in Gram-positive bacteria is distinct from that in E. coli .…”
mentioning
confidence: 99%